2002
DOI: 10.1007/s00441-002-0516-0
|View full text |Cite
|
Sign up to set email alerts
|

Localization of caveolin-3 in the sinus endothelial cells of the rat spleen

Abstract: The localization of caveolins in the sinus endothelial cells of the rat spleen has been demonstrated by confocal laser scanning and electron microscopy. Caveolin-3, a muscle-specific caveolin, was detected by Western blot analysis and immunofluorescence microscopy of isolated sinus endothelial cells and tissue cryosections of the spleen. During the immunofluorescence microscopy of isolated endothelial cells, both caveolin-3 and caveolin-1 were found. In tissue cryosections of the spleen, caveolin-3, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Cav-1 localization is dynamically regulated by both actin and tubulin in CHO cells (Mundy et al, 2002). An ultrastructural localization study of Cav-3 in splenic endothelial cells demonstrated an association with stress fibers determined to be mainly composed of actin (Uehara and Miyoshi, 2002). Regulation of the cell cytoskeleton directly by caveolins has been studied in other cell types for both Cav-1 (Shajahan et al, 2007) and Cav-3 (Head et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cav-1 localization is dynamically regulated by both actin and tubulin in CHO cells (Mundy et al, 2002). An ultrastructural localization study of Cav-3 in splenic endothelial cells demonstrated an association with stress fibers determined to be mainly composed of actin (Uehara and Miyoshi, 2002). Regulation of the cell cytoskeleton directly by caveolins has been studied in other cell types for both Cav-1 (Shajahan et al, 2007) and Cav-3 (Head et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Cav3 has been also reported in smooth muscle cells, astroglial cells (Ikezu et al, 1998), sinus endothelial cells in spleen (Uehara and Miyoshi, 2002), ciliated airway epithelial cells of the trachea and bronchial tree (Krasteva et al, 2007), and chondrocytes in the limb cartilage (Schwab et al, 1999(Schwab et al, , 2000. Although the precise function of Cav3 remains unclear, mutations or alterations of Cav3-expression are responsible for specific diseases such as cardiomyopathy, myodystrophy, and Alzheimer's disease (for review, see Quest et al, 2004).…”
mentioning
confidence: 99%
“…It is well known that the cardiac muscle cells and certain types of smooth muscle cells express both caveolin‐1 and ‐3 (Song et al, 1996; Tang et al, 1996; Hagiwara et al, 2002). Furthermore, nonmuscle cells such as the astroglial cell in the brain (Ikezu et al, 1998), sinus endothelial cells in the spleen (Uehara and Miyoshi, 2002), and chondrocytes in the limb cartilage (Schwab et al, 1999, 2000) contain caveolin‐1 and ‐3 proteins. Since the exact nature (the origin and functions) of the fibroblast‐like type B cells remains a matter for speculation, the present study was undertaken to confirm the presence or absence of caveolin‐3 in the caveolae of the type B synoviocytes in rat TMJ by immunocytochemical techniques at both light and electron microscopic levels.…”
mentioning
confidence: 99%